Consolidation of municipalities in the newest time - Y. Blagov (Правоприменение)
The subject. The article is devoted to the analysis of the causes, the process, the consequencesof the enlargement of municipalities in the Russian Federation.The purpose of this paper is to show that with the initial increase in the number of municipalities,many of them turned out to be incapable of effectively addressing local issues andproviding quality services to the population. In this regard, the reverse process began – theconsolidation of municipalities. As a result, the number of municipalities, especially the rurallevel, has dramatically decreased. The enlargement of municipal formations went arbitrarily,without taking into account the infrastructural and historical unity of the unified urbansettlements.The methodology. The author uses a dialectical method, a method of analysis and synthesis,a formal legal method, a comparative legal method.Results, scope of application. 03.04.2017 Federal Law No. 62-FZ is adopted, which providesfor the transformation of municipal raions and constituent urban and rural settlements intourban districts according to a "simplified procedure", that is, with the consent of the populationexpressed by the representative body of the municipality. In parallel, under considerationin the legal department of the State Duma of the Russian Federation there is a billintroduced by deputy A.P. Markov, offering to introduce a new type of municipal formation– the rural district. In rural districts it is proposed to unite settlements in rural municipalareas. The implementation of this bill will lead to the mass elimination of rural settlements.Actually there are no accurate and exhaustive legislative provisions regulating the territorialboundaries of urban districts, forms of the transformation and abolition of municipalities;moreover, local political and economic elites persistently seek to preserve the single tiermanagement system developed over the decades. As a result of these blemishes, within administrative areas of some RF constituent entities, there are urban districts that consist of the large not urbanized territories with a poorly developed transport, social, economic infrastructure and without any common development goals. The authors conclude that the bias towards municipalities' consolidation in many RF constituent entities is justified and caused by ignoring of the vertical command relations in former areas. At the same time, they point out the need to take into account the town-planning, economic and geographical, socio-demographic factors while transforming municipal areas into urban districts, otherwise, all these transformations are fictitious and turn into revising of powers by local elites.Conclusions. The municipal legal policy of consolidation of municipal entities is aimed at liquidating the settlement level of local self-government, which directly contradicts Part 1 of Art. 131 of the Constitution of the Russian Federation, which establishes the implementation of local self-government by the population, first of all, at the primary, settlement level.